2019
DOI: 10.1111/luts.12257
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms in detrusor underactivity: Novel experimental findings

Abstract: Underactive bladder (UAB) is a multifactorial symptom complex often related to detrusor underactivity (DU). Although recognized as a common cause of lower urinary tract symptoms and with significant effects on quality of life, UAB/DU is largely underresearched. Herein, we review upto-date knowledge on the pathophysiological mechanisms of UAB/DU, with an emphasis on the relationship between UAB and bladder outlet obstruction (BOO). Original articles and reviews concerning UAB/DU were identified through a search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 60 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…One possibility is due to a small sample size. The other possibility is that, while gender did not contribute to either detrusor overactivity or CAVI significantly in the previous studies, female gender might have lessened CAVI as suggested by a recent paper (Emi et al, 2008;Hsiao et al, 2014;Osman et al, 2018;Sakakibara et al, 2014;Smith et al, 2016;Suzuki et al, 2013;Uzun et al, 2013;Vale et al, 2019;Yeniel et al, 2018;Zacche et al, 2017). In addition, the mechanism of underactive detrusor includes 1) intrinsic detrusor muscle change by ageing, 2) secondary phenomenon by prolonged DO particularly in outlet obstruction, and 3) neural damage in the peripheral nerves (diabetes, lumbar spondylosis, etc.)…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…One possibility is due to a small sample size. The other possibility is that, while gender did not contribute to either detrusor overactivity or CAVI significantly in the previous studies, female gender might have lessened CAVI as suggested by a recent paper (Emi et al, 2008;Hsiao et al, 2014;Osman et al, 2018;Sakakibara et al, 2014;Smith et al, 2016;Suzuki et al, 2013;Uzun et al, 2013;Vale et al, 2019;Yeniel et al, 2018;Zacche et al, 2017). In addition, the mechanism of underactive detrusor includes 1) intrinsic detrusor muscle change by ageing, 2) secondary phenomenon by prolonged DO particularly in outlet obstruction, and 3) neural damage in the peripheral nerves (diabetes, lumbar spondylosis, etc.)…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the mechanism of underactive detrusor includes 1) intrinsic detrusor muscle change by ageing, 2) secondary phenomenon by prolonged DO particularly in outlet obstruction, and 3) neural damage in the peripheral nerves (diabetes, lumbar spondylosis, etc.) and/or spinal cord (DHIC as described above) (Osman et al, 2018;Vale et al, 2019). Among these, we could not answer the mechanism of prolonged DO.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our previous study using the LCS rat model, in which ONO-8055 significantly decreased MCC, 24 24,26,27 This means that UAB/DU is much more severe in the LCS model than the T1D model. In addition, the T1D model is supposed to be a myogenic rather than a neurogenic UAB/DU model, 3 while the LCS model is supposed to be a neurogenic rather This study has several limitations. First, we did not measure UPP, although a previous study showed a decrease in UPP in the LCS model after administration of TAM and ONO-8055.…”
Section: Ono-8055 Is a Highly Potent And Selective Agonist For Both Ep2mentioning
confidence: 99%
“…1 UAB is a major problem that is not well known in the public and health care sectors but is an enormous economic problem that will become more prevalent with the increasing age of populations. The etiology of UAB/DU includes aging as well as neurological diseases, and, above all, diabetic cystopathy (DC) is a major etiology of UAB/DU, [1][2][3] which affects over 50% of diabetic patients, 4 ranging from 25% to 90%. 5 The global prevalence of diabetes is estimated at 9.3% (463 million people) worldwide, and it increases with age, reaching 19.9% (111.2 million people) at 65 to 79 years old.…”
mentioning
confidence: 99%
“…The influence of pelvic arterial ischaemia on bladder function is generating increasing interest [11]. Experiments in rodents have shown that inducing ischaemia in the pelvic vasculature leads to ischaemia in the bladder wall and impaired oxygenation.…”
Section: Aetiologymentioning
confidence: 99%